Support for households due to the change in the digital terrestrial television broadcasting standard – an attempt to evaluate the adopted normative solutions - Borski, Maciej (Ius Novum, 2023)
The Act on supporting households in bearing the costs related to the change of the digital terrestrial television broadcasting standard was passed by the government on February 24, 2022, and a month later, on March 23, 2022, it was amended, because it became necessary to clarify the issue of the circle of people entitled to receive state support, which is absolutely fundamental from the point of view of this act. The content of the article will therefore be to determine the content of the normative set by interpreting the regulations of the aforementioned Act, so it takes into account all functional relationships of the standards under study and is based on all available sources of information. At the same time, when analysing statutory regulations, the author will reflect on their compliance with the principle of specificity of law, interpreted by the Constitutional Tribunal from the constitutional principle of a democratic state ruled by law.